Study on the Correlation Between Aggressive Behavior and Gut Microbiota and Serum Serotonin (5-HT) in Working Dogs - Ning Sun; Liuwei Xie; Jingjing Chao; Fuxiao Xiu; He Zhai; Yuanting Zhou; Xi Yu; Yingyi Shui (Veterinary Sciences, 2025)
Aggressive canine behavior poses a significant threat to public health. Understanding aggressive behavior is crucial for canine socialization and human–dog interactions. This study conducted an exploratory analysis of working dogs to investigate changes in gut microbiota and neurotransmitters associated with aggressive behavior. Notably, it represents the first research to systematically differentiate canine aggression into offensive and defensive subtypes for investigation. In this study, 56 working dogs from three regions of China, comprising different breeds (11 Spaniels, 13 German Shepherds, and 32 Belgian Malinois), aged 4.89 ± 1.54 years, and of both sexes (38 males and 18 females), were assessed and grouped for aggressive behavior using a C-BARQ-based questionnaire. Then, 16S rRNA sequencing and ELISA were employed to compare differences in gut microbiota and serotonin concentrations between aggressive (n = 35) and non-aggressive (n = 21) groups, as well as between offensive (n = 26) and defensive (n = 9) aggression subgroups. β-diversity analysis confirmed no significant correlation between aggressive behavior and gut microbiota composition (p > 0.05), suggesting a limited role of gut microbiota in modulating host behavior. Comparative analysis of gut microbiota composition revealed no significant differences in phylum-level abundance among different aggression types (p > 0.05). Notably, the non-aggressive group exhibited significantly higher relative abundances of Escherichia-Shigella, Erysipelotrichaceae_UCG-003, and Clostridium_sensu_stricto_1 compared to the aggressive group (p < 0.05). Random forest analysis identified Lactobacillus as a biomarker for canine aggressive behavior and Turicibacter as a discriminatory factor between offensive and defensive aggression. The results demonstrated a strong correlation between aggression and 5-HT neurotransmission. Serum serotonin levels were significantly lower in both the defensive (39.92 ± 2.58 ng/mL) and offensive (50.07 ± 3.90 ng/mL) aggression groups compared to the non-aggressive group (59.49 ± 2.76 ng/mL), with the lowest levels found in defensively aggressive dogs. The defensive group showed significantly lower serotonin levels than the offensive group (p < 0.001). The results demonstrate that different behavioral phenotypes in aggressive dogs lead to distinct gut microbiome compositions. This suggests that microbiome analysis may facilitate early diagnosis and preventive intervention before aggressive behavior manifests. As such, 5-HT shows potential as a monitoring tool for diagnosing canine aggression, with significant practical applications in canine behavior management.